ERT 2013 - Vardopoulos, Panos (Design/Arts/Culture, 2022)
In June 2013, the memorandum Greek government decided to shut down the public radio and television broadcaster, ERT. This is a photographic documentary of the anti-government protests in the courtyard of ERT headquarters, during the occupation of the premises by the majority of employees, trying to keep the voice of public broadcaster alive.